Treatment of medication‐related osteonecrosis of the jaw using segmental mandibulectomy and a reconstruction plate: A case report and 5‐year follow‐up. Issue 1 (4th March 2021) - Kamaguchi, Mayumi; Ohga, Noritaka; Hata, Hironobu; Yoshikawa, Kazuhito; Sakata, Ken‐Ichiro; Asaka, Takuya; Sato, Jun; Kitagawa, Yoshimasa
Abstract: Medication‐related osteonecrosis of the jaw (MRONJ) has been commonly known as a adverse side effect of antiresorptive or antiangiogenic agents for the treatment of osteoporosis patients. Although there is considerable evidence on the occurrence of MRONJ in the literature, the number of studies focusing on Stage 3 MRONJ attributable to oral administration of bisphosphonates (BPs) in patients with osteoporosis is limited. The patient had exposed necrotic bone in the mandible and pus discharge through an extraoral fistula attributed to an oral BPs for the treatment of steroidal osteoporosis. She was diagnosed with Stage 3 MRONJ. She had no other identifiable cause of mandible necrosis. Given the severity and risk of pathological fractures of the mandibular bone, an extensive surgical therapy was performed after failure of compressive conservative therapy. Our surgical treatment satisfied the patient with regard to esthetics, leading to a dramatic improvement in her quality of life for 5 years after surgery. We report a case of Stage 3 MRONJ associated with BP administration for steroid‐induced osteoporosis and discuss esthetically successful reconstruction of the mandible using mandibular reconstruction plates following segmental mandibulectomy. To prevent such severe complications, it is important to develop appropriate medical and surgical treatment strategy for immunosuppressed patients with osteoporosis.